Development of Flowrate Measurement System and Variable Area Flow Meter Calibration - Pornpatkul, Chatchaval; pattanapong, Yongyut (Journal of Advanced Development in Engineering and Science, 2023)
This paper discusses the development of flow measurement of liquid. The Rota flow meter was used to measure the volumetric flowrate and was tested with a calibrated flowrates, which are a standard tool Piston Prover in reference flowrate to be measured. The rate of flow meter was measured by Rota flow meter in a range of 0.5 - 5 gpm, with the accuracy ± 2% of FS. (± 0.1 gpm). The results of all the measurement ranges appear that the maximum error is +0.011 gpm at 2.0 gallons per minute. The expanded uncertainty in measuring was calculated at this position that the calculated value is ± 0.02 gpm. When this value was combined with the error measurement + 0.011 gpm, it was found that the errors included the uncertainty were still in the accuracy of Rota flow meter. In conclusion, this Rotary meter has the appropriate status and can be efficiently applied.